Qual o resultado de
![- 2x - ( - 3x + 8) = - 7x + 15 - 2x - ( - 3x + 8) = - 7x + 15](https://tex.z-dn.net/?f=++-+2x+-+%28+-+3x+%2B+8%29+%3D++-+7x+%2B+15)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
Equação do primeiro grau :
-2x - (-3x + 8) = -7x + 15
-2x + 3x - 8 = -7x + 15
x - 8 = -7x + 15
x + 7x = 15 + 8
8x = 23
x = 23/8
Espero ter ajudado bastante!)
Perguntas interessantes
Matemática,
10 meses atrás
Geografia,
10 meses atrás
História,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás